Pemanfaatan Limbah Botol Plastik untuk Pembuatan Buket Bunga sebagai Peluang Berwirausaha - Dea Ayuk Septiani; Agus Susanti; Sofia Daniati (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2025)
Plastic bottle waste is a leftover material that is no longer used from human activities. Flower bouquet has become one of the necessities, especially for teenagers to adults. Comparison of the price of a bouquet of real flowers and artificial flowers is quite expensive, making a bouquet of flowers from plastic bottle waste a new innovation. The purpose of this study was to determine the process of making a flower bouquet, determine product validation, determine the public acceptance of the product, and determine the comparison of the price of production costs of a flower bouquet of plastic bottle waste, real flowers, and artificial flowers. This research uses the methods of observation, literature, experimentation, documentation, interviews, and questionnaires. The process of making a bouquet consists of the preparation of tools and materials, and manufacturing steps starting from bottle selection, bottle cleaning, bottle formation according to flower patterns, pattern assembly, application of color paint, glitter, and clear paint. Making a flower bouquet from plastic bottle waste was carried out through three experiments. The results of the validation test to 3 expert validators based on the assessment of shape, color, appearance, circuit patterns, and color combinations that obtained decent results were the products in the third experiment with a score of 15. The results of the public test to 34 respondents on the public acceptance of the products in the third experiment based on aspects of shape, color, appearance, circuit patterns, and color combinations were very like (score 3). So that the product in the third experiment was accepted by the community. So that the product in the third experiment is accepted by the public and has the potential to become a business opportunity. We recommend that craftsmen streamline time in the manufacturing process and use gloves to avoid droplets of wax glue and cuts due to cutters or sharp bottle parts.